Silane as adhesion promoter in damaged areas - Deyá, Marta Cecilia (2016)
Silanes have been studied as adhesion promoters between metals (aluminum, galvanized steel and steel) and paints such as polyurethanes. The objective of this work was to study γ-glycidoxypropyltrimethoxysilano (glymo) as adhesion promoter between sandblasted steel and one water-based epoxy paint formulated in the laboratory. In some cases, the silane film was doped with sodium phosphate or sodium benzoate, and in other cases, glymo or extra epoxy resin were incorporated as part of the paint formulation. The performance of the metal-glymo-paint system was studied by electrochemical noise technique and accelerated tests (salt spray cabinet and humidity chamber). Dry and wet adhesions were also determined. The results showed that the incorporation of γ-glycidoxypropyltrimethoxysilane as pretreatment or in paint formulation does not enhance paint adhesion in undamaged areas. However, when the painted area was damaged, the incorporation of silane in the paint or doped silane in the pretreatment enhances paint performance in these areas.